Structural assessment of classical poems before and after 1357 - محمّد حسن حائری; مهدی رضا کمالی بانیانی (تاریخ ادبیات)
Persian poetry undoubtedly has a bright and proud past. If Iran's literature had nurtured only the words of poets such as Ferdowsi, Nizami, Khayyam, Rumi, Saadi and Hafiz in its past history, it would have deservedly been respected. But this is despite the fact that the honors of Iran's past poetry are not limited to these high peaks. Nima's loud cry was so effective that it shook the eardrums of some traditionalist poets and broke some of their dogmas. Therefore, poets such as: Parviz Natel-Khanlari, Mohammad Hossein Shahriar, Mehrdad Avesta, Hossein Monzavi, etc., influenced by the modernist currents of contemporary poetry, each of them innovated in different ways in the forms of Persian poetry and experienced new spaces. Therefore, in this article, the comparison and analysis of traditional poetry after the Islamic Revolution with classical poetry has been discussed in terms of structure.